Evaluation of fatigue in semi-professional football players: association between overtraining and physical fitness - Nikolaidis Pantelis T. (Sciendo, 2014)
Study aim: overtraining (OT) has a detrimental effect on sport performance, but it is not clear to what extent it influences physical fitness. The aim of this study was to examine the relationship between OT and physical fitness in football players.